التفسير المقاصدي لآيات الصيام في تفسير التهانوي: Intentional Interpretation of Fasting Verses in The Provisions of The Qur'an by Al-Tahanawi - Umar Farooq,; Dr. Tahir Mehmood , (Al Manhal Research Journal, 2024)
Fasting is an act of worship of great significance in Islam and has a powerful impact on achieving piety. It weakens the carnal desires in the fasting person, which helps in repelling lustful temptations. Through fasting, a person draws closer to Allah, Almighty and Exalted, because when the soul is purified from inclinations towards sins, it naturally prefers obedience over disobedience, thus achieving piety. The human being is composed of both angelic and animalistic aspects. The animalistic aspect increases with excessive eating and drinking, which boost physical strength, while the angelic aspect increases with frequent turning to Allah Almighty. The more one engages in worship and turns to Allah Almighty, the more their spiritual and angelic strength increases, bringing them closer to Allah, Almighty and Exalted. When the animalistic aspect becomes stronger and overpowers the angelic strength, satanic whispers increase in the heart, and the soul becomes averse to acts of obedience and feels burdened by them. Conversely, when the angelic aspect becomes stronger and overpowers the spiritual, satanic whispers decrease in the heart, and the soul finds pleasure in acts of obedience and desires to increase them. Therefore, a servant must ensure that their angelic strength does not become weaker than their animalistic strength, which can be achieved through frequent fasting. This is why Allah Almighty has prescribed fasting for the servant to attain piety and to strengthen their angelic strength over the animalistic. Fasting in Islam has many purposes, and Allah Almighty has revealed numerous verses regarding it. Scholars have interpreted these verses with a focus on their interpretation and have elucidated the wisdom behind fasting. Among these scholars are the authors of "Ahkam al-Qur'an" by al-Tahanawi, who provided an Intentional interpretation of the verses on fasting. The researcher aims to present and clarify an Intentional interpretation of the verses on fasting from "Ahkam al-Qur'an" by al-Tahanawi, so the reader can understand the purposes of fasting.